Coronectomy - A viable alternative to prevent inferior alveolar nerve injury - Sagtani, Alok; Sagtani, Reshu Agrawal; Jaisani, Mehul; Pradhan, Leeza (Journal of College of Medical Sciences-Nepal, 2015)
Background and Objectives: Coronectomy is a relatively new method to prevent the risk of Inferior Alveolar Nerve (IAN) injury during removal of lower third molars with limited scientific literature among Nepalese patients. Thus, a study was designed to evaluate coronectomy regarding its use, outcomes and complications. Materials and Methods: A descriptive study was conducted from December 2012 to December 2013 among patients attending Department of Oral and Maxillofacial Surgery, College of Dental Sciences, BP Koirala Institute of Health Sciences, Dharan, Nepal for removal of mandibular third molars. After reviewing the radiograph for proximity of third molar to the IAN, coronectomy was advised. A written informed consent was obtained from the patients and coronectomy was performed. Patients were recalled after one week. The outcome measures in the follow-up visit were primary healing, pain, infection, dry socket, root exposure and IAN injury. The prevalence of IAN proximity of lower third molars and incidence of complications were calculated. Results: A total 300 mandibular third molars were extracted in 278 patients during the study period. Out of 300 impacted mandibular third molar, 41 (13.7%) showed close proximity to inferior alveolar nerve . The incidence of complications and failed procedure was 7.4% among the patients who underwent coronectomy. During the follow up visit, persistent pain and root exposure was reported while other complications like inferior alveolar nerve injury, dry socket and infection was not experienced by the study patients. Conclusion: With a success rate of 92.6% among the 41 patients, coronectomy is a viable alternative to conventional total extraction for mandibular third molars who have a higher risk for damage to the inferior alveolar nerve. JCMS Nepal. 2015;11(3):1-5.